PELAKSANAAN PROMOSI MELALUI MEDIA SOSIAL PADA OBJEK WISATA DAKWAH OKURA KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Suryadi, Meity Intan; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Promotion is part of marketing, namely to encourage, persuade, inform, explain, and their recalling a product both goods and services. With the implementation of the promotion is done in an attraction make the object easier to be known and recognized by potential visitors, so visitor are easy to reach tourism object. This research used a descriptive quantitative method to examine the problems. For first goals, used triangulation technique and for second goals used percentation technique. The samples in this research were 100 respondents, who were taken by using accidental sampling. While data collection techniques in this research using observation, interview, and questioner. The results of research Promotion Implementation via Social Media in Wisata Dakwah Okura Object Rumbai Pesisir District Pekanbaru City is managers have used 3 social media which are fanspage facebook, twitter, and instagram for promotion. Based on respondent respons, promotion mix or sub-variables on promotion via social media (Sunyoto, 2012) are divided into the Advertising 75,7%, Sales Promotion 51,4%, Public Relation 78,3%, and Word of Mouth Marketing 60,8%. Overall, promotion implementation via social media in Wisata Dakwah Okura object has been accomplished in the amount of 66,4%Keywords: Advertising, Promotion, Public Relation, Sales Promotion, Social Media, Word of Mouth Marketing